Volume 1: 20th Biennial Conference on Mechanical Vibration and Noise, Parts A, B, and C 2005
DOI: 10.1115/detc2005-84312
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Investigation of Hopf Bifurcations Occurring in a 1DOF Sliding-Friction Oscillator With Application to Disc-Brake Vibrations

Abstract: This article deals with analytical investigations on stability and bifurcations due to declining dry friction characteristics in the sliding domain of a simple disc-brake model, which is commonly referred to as “mass-on-a-belt”-oscillator. Sliding friction is described in the sense of Coulomb as proportional to the normal force, but with a friction coefficient μS which depends on the relative velocity. For many common friction models this latter dependence on the relative velocity can be described by exponenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…Basically, two phenomena can be distinguished, referred to as squeal and groan. In both cases the entire brake assembly, comprising the pads, the caliper and the disc, exhibits coupled lateral motions [3]. Though, the basic mechanisms triggering and feeding this lateral vibrations are still in doubt.…”
Section: Application To Disc-brake Groanmentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, two phenomena can be distinguished, referred to as squeal and groan. In both cases the entire brake assembly, comprising the pads, the caliper and the disc, exhibits coupled lateral motions [3]. Though, the basic mechanisms triggering and feeding this lateral vibrations are still in doubt.…”
Section: Application To Disc-brake Groanmentioning
confidence: 99%
“…12(b) shows power spectral densities of the in-plane motion and the acoustic signal: it is found, that the dominant spectral contents of the acoustic measurement do not match the frequency of the in-plane motion of the pad. As described in [3], the noise is emitted by bending modes of the disc, which are coupled to tilting motions of the saddle. By simulation it is found that one trigger-mechanism of the latter motions could be translational oscillations of the pads.…”
Section: Application To Disc-brake Groanmentioning
confidence: 99%
“…5). This model seems quite advantageous, since it catches the measured mean value curve of m very good, while it only demands two parameters D m, a [5]. It shall be mentioned, that expanding the exponential function into a series and truncating it after the linear term yields…”
Section: Characteristic Showing Exponential Decaymentioning
confidence: 99%
“…Investigations of a deterministic nonlinear oscillator with parameters according to measurements, show good correspondence to the observed ending point of the vibrations. Albeit, the model does not explain why the real system does not reach the stick-slip limit-cycle [2]. Another possible explanation is, that the displayed variables only span a sub-space of the state-space, which has a dimension too small to contain the periodicity.…”
Section: Discussionmentioning
confidence: 95%